2003
DOI: 10.1127/lr/14/2003/65
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of the macrophytic vegetation in the running waters of the Friedberger Au (near Augsburg, Germany)

Abstract: The macrophytic vegetation of the Friedberger Ach, a tributary to the River Danube, and of three bordering ground water ditches was mapped six times within the period from 1972 to 1996 using the same method. Different characteristic features have been calculated by means of quantitative evaluation methods using the data available from this long-term study. The temporal dynamics of the macrophytic vegetation based on these studies over a 24 years period could be analysed using the "Relative Plant Quantity" (RPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…both species were occurring during winter and pre-monsoon seasons only (Table 5). Hrivnak et al (2006), Veit and Kohler (2003), Mahapatra et al (2011) also found similar trends of results in their respective studies. The summary of overall observation of identification of tolerant and sensitive aquatic macrophytes grown in the respective selected study areas are shown in Table 6.…”
Section: Ken Riversupporting
confidence: 67%
“…both species were occurring during winter and pre-monsoon seasons only (Table 5). Hrivnak et al (2006), Veit and Kohler (2003), Mahapatra et al (2011) also found similar trends of results in their respective studies. The summary of overall observation of identification of tolerant and sensitive aquatic macrophytes grown in the respective selected study areas are shown in Table 6.…”
Section: Ken Riversupporting
confidence: 67%
“…In the last decade, mapping of macrophytes and studies of interaction between macrophytes and environment in running waters were very intensive in Danube countries e. g. Germany (Veit & Kohler, 2003), Austria (Janauer & Wychera, 2000), Hungary (Pall et al, 1996), Serbia and Montenegro (Vukov et al, 2003) and Romania (Sarbu, 2003). In the territory of Slovakia, only few data have been published (Hrivnák et al, 2003(Hrivnák et al, , 2004Oťaheľová & Valachovič, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the rivers flowing through agricultural landscapes are often exposed to high influxes of nutrients, as well as morphological alterations, both of which negatively influence the biodiversity of riverine ecosystems [ 23 ]. Beside the valuable role of macrophytes as the indicators of the current human pressure, aquatic macrophytes have been used by many researchers to monitor the long-term changes in rivers [ 24 , 25 , 26 , 27 , 28 , 29 ], as well as in lakes [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%